Finansiranje sporta i sponzorstvo - Mićović, Miodrag (Array, 2019)
Sponsorship, especially when it comes to professional sports, has a special significance for financing this kind of sporting activities. Namely, sponsorship is in the function of efficient satisfaction of sponsor's interests, which is reflected in maximization of his presence and public recognition through the interconnection with the carrier of some sporting content. At the same time, thanks to sponsorship, sponsored party acquire the ability to achieve better and more prestigious results than others. Since sponsorship has its own specificities, which clearly distinguish it from other contractual relationships, author pointed out: the concept of sports sponsorship; the importance of the sponsored party’s image and the right to use the image, which the sponsor acquires upon conclusion of the contract; the relationship between individual and collective image; limitations for establishing and implementing sponsorship.